Domesticating Money and Prices in Postcapitalism: the Example of Commonism - Dufour, Mathieu; Tremblay-Pepin, Simon (Université d'Ottawa | University of Ottawa, 2026)
This article reviews Commonism, a postcapitalist model developed by Stefan Meretz and Simon Sutterlütti (2023; 2025; Gerdes et al. 2023) based on a decentralized network of commons. As this model puts forward the idea that a postcapitalist economy should avoid using money at all, we focus specifically on how economic coordination can be realized in Commonism. We first present how we understand the functioning of Commonism, to then underline issues generated by the absence of the money form. These issues are about human volition, information, social arbitration and temporality. We end by suggesting a way to domesticate money that would resolve the problems we’ve identified without doing much harm, in our view, to the main features of the model.
This version of the article has been accepted for publication, after peer review (when applicable) and is subject to Springer Nature’s AM terms of use, but is not the Version of Record and does not reflect post-acceptance improvements, or any corrections. The Version of Record is available online at: http://dx.doi.org/10.1007/s43253-026-00174-8
Keywords: Commonism; Postcapitalism; Money